2011
DOI: 10.1103/physrevb.83.064106
|View full text |Cite
|
Sign up to set email alerts
|

Shear response ofΣ3{112}twin boundaries in face-centered-cubic metals

Abstract: Molecular statics and dynamics simulations were used to study the mechanisms of sliding and migration of 3{112} incoherent twin boundaries (ITBs) under applied shear acting in the boundary in the face-centered-cubic (fcc) metals, Ag, Cu, Pd, and Al, of varying stacking fault energies. These studies revealed that (i) ITBs can dissociate into two phase boundaries (PBs), bounding the hexagonal 9R phase, that contain different arrays of partial dislocations; (ii) the separation distance between the two PBs scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 54 publications
(82 reference statements)
8
57
0
Order By: Relevance
“…In twinned Al, the ITB migration-accommodated plasticity at greater stress can be explained by the interface disconnection glide mechanism revealed by MD simulations 14 . First, lattice dislocations dissociate at the ITB, causing its migration accompanied by load drop.…”
Section: Itbmentioning
confidence: 99%
See 1 more Smart Citation
“…In twinned Al, the ITB migration-accommodated plasticity at greater stress can be explained by the interface disconnection glide mechanism revealed by MD simulations 14 . First, lattice dislocations dissociate at the ITB, causing its migration accompanied by load drop.…”
Section: Itbmentioning
confidence: 99%
“…The majority of prior studies focused on metals with low stacking-fault energy (SFE) (Cu, Ag) and/or a low ratio of unstable twinning (g ut ) to unstable stacking energy (g us ), because twins readily form in such metals during growth or deformation [10][11][12][13] . Although the density of incoherent twin boundaries (ITBs) is typically lower than that of CTBs, both CTBs and ITBs have been found to play crucial roles in plastic deformation in nt metallic materials with low SFE; CTBs act as barriers for slip, but ITBs can easily migrate in association with detwinning 14,15 . Furthermore, the deformation mechanisms of nt metals with extremely fine nanotwins are dominated by Shockley partial dislocations 4 , which are mostly nucleated from ITBs.…”
mentioning
confidence: 99%
“…This is equivalent to separately considering the displacements of the pure step component and those of the dislocation and then adding them. This method has been programmed for simulations of dislocations and twins in face-centered cubic (fcc) and body-centered cubic structures [55,56], and extended for dislocations and twins in hcp structure [57]. After a TD glides, remote atoms above and below the shear plane experience a relative displacement of b t .…”
Section: Twinning Disconnectionsmentioning
confidence: 99%
“…Compared to coherent Σ3{111} twin boundaries, Σ3{112} incoherent twin boundaries (ITBs) have been less studied. 36,37 It has been found that the Σ3{112} ITBs have a larger mobility than coherent twin boundaries. According to Li et al, 38 slip bands can transmit through ITBs in Cu, and the penetrability and mobility of the ITBs contribute to a higher fatigue cracking resistance.…”
mentioning
confidence: 99%